The impact of strategic knowledge on strategic improvisation: an exploratory study of some private hospitals in the city of Baghdad - ابتسامة رعد ابراهيم; الاء عبد الكريم غالب المدو; علي عدنان حسن (مجلة الغري للعلوم الاقتصادية والادارية)
The current study aimed to know the role that strategic knowledge plays on strategic improvisation in private hospitals (the Royal Hospital, Al-Salama Hospital, Al-Karkh Al-Ahli Hospital, and Al-Shifa Hospital). To achieve the objectives of the study, the descriptive analytical approach was adopted, where the researchers developed a questionnaire consisting of (30) items. A random sample was drawn so that the study sample consisted of (103) workers in private hospitals, and the results were analyzed based on the (SPSS) program and descriptive statistics tools. It was concluded that private hospitals currently have a great interest in the strategy of strategic knowledge and strategic improvisation, and provide services It is of high quality and attracts highly experienced doctors. Strategic knowledge is closely linked to strategic improvisation. It has been concluded that private hospitals’ use of strategic knowledge contributes to increasing strategic improvisation